Case report- a rare survival of 2,4-D (ethyl ester) ingestions - Tiwari, Arun; Singh, V. B.; Kumar, Deepak; Meena, B. L. (International Journal of Research in Medical Sciences, 2017)
2,4-Dichlorophenoxyacetic acid (usually called 2,4-D) is a widely used systemic herbicide. Ingestion of 2,4 D (Ethyl Ester) is rarely reported. Ingestion of this substance leads to neurotoxicity, cardiotoxicity, hematotoxicity and nephrotoxicity. Previously reported cases describe toxicities of this agent with very high fatality, only 2 survived case reports are available. In our case the substance was identified readily and treatment started within hours of ingestion with prompt gastric lavage and forced alkaline diuresis. At the time of admission patient had already lost consciousness (i.e. neurotoxicity), patient had developed muscle fibrillations and fasciculations (i.e. myotoxicity) and during the hospital stay he got acute kidney injury (i.e. nephrotoxicity) but all toxicities recovered with treatment. Previously reported fatal cases had late identification of substance and only symptomatic supportive treatment was given whereas we used aggressive approach with forced diuresis and haemodialysis. We are reporting third survived case of 2,4-D (Ethyl Ester) poisoning and emphasizing key points in the management, early identification of substance, early institution of forced alkaline diuresis and use of renal function tests as prognostic marker with timely hemodialysis.